Pembelajaran Ansambel Sejenis Kelas VIII Di SMP Angkasa Lanud Padang - Wulandari, Kiki; Yensharti (Universitas Negeri Padang, 2023)
The purpose of this study was to describe the Class VIII Same-Sex Ensemble learning at SMP Angkasa Lanud Padang. This type of research is a qualitative research with descriptive method. The object of research is class VIII.1 students with a total of 28 students. The data collection technique is carried out by observation and direct observation of how similar ensemble learning is. As for data analysis techniques by identifying, classifying, writing reports and concluding data. Based on the results of the research obtained, that the implementation of Class VIII Ethical Ethical Ensemble learning at SMP Angkasa Lanud Padang has been carried out well in semester 2 of the 2023/2024 academic year. In the learning process the teacher carries out the lesson in accordance with the lesson plan that has been prepared. The delivery of learning objectives and the material given by the teacher to students at each meeting can be understood and understood properly. The use of learning methods and media by teachers can create a pleasant learning atmosphere for students. An understanding of similar music ensembles and techniques for playing the recorder as a group can be carried out by students well. Playing the recorder individually and in groups can be carried out by students well. Students can play the Teacher's Hymn individually and in groups according to the sheet music given by the teacher. The results of the assessment carried out by the teacher on students showed good results from the 28 people who attended, only 2 people who had not finished.